UNIKNYA MEMAHAMI TASAWUF DAN AJARANNYA - Asmaul Husna; Mahbuby, Achmad; Muhammad Rahmatullah (Program Studi Ilmu Tasawuf IAI Pangeran Diponegoro Nganjuk, Jawa Timur, 2024)
ABSTRACTThe science of Sufism is the study of procedures for cleansing the heart from arrogance, joy, envy, envy and so on.By filling it with praiseworthy qualities through the predetermined maqam maqam, as well as in riyadhah and mujhahadah, with the aim of bringing oneself closer to Allah SWT so that one can feel the presence of God within oneself, and can become a person who has good noble character, good manners and manners. his daily life.Studying Sufism is not deviant, because many people think that studying Sufism is deviant,but studying this science also imitates the simple life of the Prophet Muhammad.Here we use a qualitative method which also includes references from various published journals, which by using this method we can conclude the history, development and state of mind in the science of Sufism. In living as a Sufist you need to take several states, including: repentance, asceticism , wara', khauf, raja' and so on. For people who are serious about practicing Sufism, there is no doubt that that person only depends on Allah SWT, and will no longer have negative prejudices against the Creator, because the strength of his faith and devotion makes him feel close to Allah SWT and truly feel that he is under the supervision of the creator.